Cost‐effectiveness of a combined physical exercise and psychosocial training intervention for children with cancer: Results from the quality of life in motion study. (10th October 2016) - Braam, K.I.; van Dijk‐Lokkart, E.M.; van Dongen, J.M.; van Litsenburg, R.R.L.; Takken, T.; Huisman, J.; Merks, J.H.M.; Bosmans, J.E.; Hakkenbrak, N.A.G.; Bierings, M.B.; van den Heuvel‐Eibrink, M.M.; Veening, M.A.; et al.
Abstract : This study was performed to estimate the cost‐effectiveness of a combined physical exercise and psychosocial intervention for children with cancer compared with usual care. Sixty‐eight children, aged 8–18 years old, during or within the first year post‐cancer treatment were randomised to the intervention ( n  = 30) and control group ( n  = 38). Health outcomes included fitness, muscle strength and quality adjusted life years; all administered at baseline, 4‐ and 12‐month follow‐up. Costs were gathered by 1 monthly cost questionnaires over 12 months, supplemented by medication data obtained from pharmacies. Results showed no significant differences in costs and effects between the intervention and control group at 12‐month follow‐up. On average, societal costs were €299 higher in the intervention group than in the control group, but this difference was not significant. Cost‐effectiveness acceptability curves indicated that the intervention needs large societal investments to reach reasonable probabilities of cost‐effectiveness for quality of life and lower body muscle strength. Based on the results of this study, the intervention is not cost‐effective in comparison with usual care.